"As time goes by": Econometric estimation of the Prosecco life cycle - Laura Onofri; Vasco Boatto (Economics and Econometrics Research Institute (EERI), 2022)
This paper presents an empirical model that estimates the Prosecco life cycle. We use OLS and 3SLS to estimate the life cycle of Prosecco (1) worldwide, (2) as a system of equations in selected countries and (3) as a system of equations in comparison with Cava and Champagne. Our results reveal that Prosecco is approaching maturity worldwide, different from Cava and Champagne, which have already achieved that phase. The Prosecco life cycle is in the growing phase in Germany, China and Japan, in the maturity phase in France, the United Kingdom and the U.S. and in the declining phase in Russia.
Keywords: C2; C51; C54; L1; 330; Product life cycle; Prosecco CDO; life cycle empirical specification; 3SLS; OLS